Analysis of Service Quality, Motivation, and Level of Consumer Confidence in Purchasing Decisions at PT. Aksara Sukses Makmur Medan - Jingga, Juan Cahyadi; Nazmi, Hendra; Dewi, Sri Puspa (GoAcademica Research & Publishing, 2023)
This study aims to investigate how customer confidence, motivation, and service quality affect purchases made at PT. Aksara Sukses Makmur Medan. This study is descriptive in nature. Saturated sampling is the method used in this study, with the population and sample consisting of 77 enterprises that are users of PT. Aksara Sukses Makmur Medan. Analysis using multiple linear regression is the statistical technique employed. The findings indicated that customer confidence in purchase decisions, motivation, and service quality were all somewhat influenced. Additionally, it asserts that customer confidence in their purchase decisions, motivation, and service quality are all influenced at the same time. The magnitude of the coefficient of determination is 70% and the remaining 30% is explained by other variables that are not discussed in this study.